Duplication of 10q24.31 in a family with congenital nystagmus and split-hand/foot malformation - SÖYLEMEZ, MEHMET ALİ; GEÇKİNLİ, BİLGEN BİLGE; GÜNEY, AHMET İLTER; ATA, PINAR; ARMAN, AHMET (My University, 2021)
Introduction: Split-hand/split-foot malformation (SHFM),also known as ectrodactyly,is a congenital limb malformation caused by absence of central rays. Phenotypic spectrum can range from a median cleft of the hand and/or foot to monodactyly. It occurs in 1/8500-1/25000 newborns. It can be isolated or with various syndromes. For isolated types seven loci were found responsible. However molecular mechanism was not elucidated in split-hand with congenital nystagmus,fundal changes,and cataracts syndrome (OMIM:183800), also known as KarschNeugebauer syndrome (KNS). Cases: Five-month-old female patient was referred to our clinic because of having SHFM. SHFM was detected by prenatal USG. Natal and postnatal histories were normal. Opththalmological consultation revealed congenital nystagmus,and strabismus. Her growth parameters were normal. Strabismus,nystagmus,epicanthus,upslanting palpebral fissures, flattened nasal root,anteverted nares,micrognathia,and monodactyly of four limbs were detected. Her mother had also similar phenotype. No additional anomaly was detected in both. A-CGH analysis revealed 419,9 kb heterozygous duplication in 10q24.31 containing LBX1, BTRC, POLL, FBXW4 genes. Segregation studies still continue. Discussion: Although SHFM3 is one of the most common types of SHFM, nystagmus had not been reported in any patient in the literature. On the other hand,SHFM and nystagmus are the key features in the KNS. Herein we report a family with KNS harboring the duplication of 10q24.31. To best of our knowledge this is the first report to illuminate the molecular mechanism of KNS. More cases and functional studies are needed to distinguish whether SHFM3 and KNS are same or different entity.
Keywords: 10q24.31; SHFM; Ectrodactyly; Nystagmus; Karsch-Neugebauer